Polarizing sheets, heat-bent molded products, and sunglasses
Patent Information
- Application Number
- JP2025058928
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166153000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing sheet, a thermally bent molded article, and sunglasses.
Background Art
[0002] Currently, polarizing sheets that have been put into practical use typically employ a polarizing film obtained by adsorbing or impregnating polyvinyl alcohol (PVA) with iodine or a dichroic organic dye. This polarizing film is usually provided with a transparent resin such as triacetyl cellulose as a protective film for the polarizing film on one or both sides thereof, to form a polarizing sheet (sometimes referred to as a polarizing plate) that is easy to handle, suitable for secondary processing, inexpensive, and lightweight.
[0003] Here, when a polarizing sheet is used in applications requiring impact resistance, for example, in a polarizing lens for sunglasses, a polarizing film protective film such as a polycarbonate film (sometimes referred to as a resin layer or a polarizing film base material) is laminated on both sides of a polarizing film using a dichroic organic dye to form a polarizing sheet, which is punched into a desired shape, thermally bent into a partial spherical surface, and appropriately subjected to surface treatment or the like for production. As such a polarizing sheet for thermal bending, for example, the one described in Patent Document 1 is known.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problems to be Solved by the Invention
[0005] Here, when heat-bending a polarizing sheet, which has thermoplastic resin layers laminated on both sides of a polarizing film, it is desirable to perform the heat bending at a temperature where the X-curve value and Y-curve value of the thermoplastic resin layer intersect. Specifically, Figure 1 is a schematic diagram showing an example of a polarizing sheet cut to the size of sunglasses, and 10 shows a polarizing sheet that has been punched out for sunglasses. The punched polarizing sheet is heat-bent to process it into the shape of a lens with a predetermined curve. Here, if the stretching direction of the thermoplastic resin layer is the X direction and the direction perpendicular to the stretching direction is the Y direction, it is desirable that the curve value showing the bending curve in the X direction (X-curve value) and the curve value showing the bending curve in the Y direction (Y-curve value) are approximately the same when heat-bending is performed at a certain temperature. By heat-bending at the temperature where the X-curve value and Y-curve value intersect (intersection temperature), it is possible to make a lens with uniform curve values in each direction. However, if the above intersection temperature is too high, it will be the temperature at which the lens shrinks, resulting in a lens smaller than the desired size. Furthermore, even if heat bending is possible, if the formability is poor, good heat bending processability cannot be achieved. The present invention aims to solve these problems and to provide a polarizing sheet with a low cross-temperature and excellent shapeability, as well as a heat-bent molded article and sunglasses. [Means for solving the problem]
[0006] Under the above-mentioned problems, the inventors conducted investigations and found that the above problems can be solved by adjusting the glass transition temperature of the polarizing sheets on both sides of the polarizing film. Specifically, the above problem was solved by the following means. [1] The first resin layer, the polarizing film, and the second resin layer are arranged in the order described above. The glass transition temperature Tg1 (unit: °C) of the first resin layer and the glass transition temperature Tg2 (unit: °C) of the second resin layer are, Tg2-Tg1≧-1 Satisfying the conditions, The retardation of the first resin layer (Re1) and the retardation of the second resin layer (Re2) are, respectively, 2500nm ≤ Re1 ≤ 8000nm, and 0 ≤ Re2 ≤ 500nm A polarizing sheet that satisfies the requirements. [2] The polarizing sheet according to [1], wherein the glass transition temperature Tg1 of the first resin layer and the glass transition temperature Tg2 of the second resin layer satisfy Tg2-Tg1≧0. [3] The polarizing sheet according to [1], wherein the glass transition temperature Tg1 of the first resin layer and the glass transition temperature Tg2 of the second resin layer satisfy Tg2-Tg1>0. [4] The polarizing sheet according to any one of [1] to [3], wherein the thickness of the first resin layer and the thickness of the second resin layer are each independently 100 to 500 μm. [5] The polarizing sheet according to any one of [1] to [4], wherein the first resin layer and the second resin layer each independently contain polycarbonate and / or polyamide. [6] The polarizing sheet according to any one of [1] to [5], wherein the first resin layer is a stretched film and the second resin layer is a non-stretched film. [7] The glass transition temperature Tg1 of the first resin layer and the glass transition temperature Tg2 of the second resin layer satisfy Tg2-Tg1>0, The thickness of the first resin layer and the thickness of the second resin layer are, independently, 100 to 500 μm. The first resin layer and the second resin layer each independently contain polycarbonate and / or polyamide. The first resin layer is a stretched film, and the second resin layer is an unstretched film. A polarizing sheet as described in any one of [1] to [6]. A heat-bent molded polarizing sheet as described in any one of [8][1] to [7]. [9] The heat-bent molded article according to [8], wherein the first resin layer side is a curved convex surface and the second resin layer side is a curved concave surface. Sunglasses including the heat-bent molded body described in
[10] [8]. [Effects of the Invention]
[0007] The present invention makes it possible to provide polarizing sheets with low cross-temperature and excellent formability, as well as heat-bent molded articles and sunglasses. [Brief explanation of the drawing]
[0008] [Figure 1] This is a schematic diagram showing an example of a polarizing sheet cut to the size required for sunglasses. [Figure 2] This is a schematic diagram illustrating an example of the layer structure of a heat-bent molded body. [Modes for carrying out the invention]
[0009] The following describes in detail embodiments for carrying out the present invention (hereinafter simply referred to as "this embodiment"). Note that the following embodiment is illustrative for explaining the present invention, and the present invention is not limited to this embodiment. In this specification, "~" is used to mean that the numerical values before and after it are included as the lower and upper limits. Furthermore, the upper and lower limits of the numerical values in this specification are given as examples of this embodiment, regardless of the combination of upper and lower limits. In this specification, a preferred combination of embodiments is a more preferred embodiment. In this specification, all physical properties and characteristic values shall be those at 23°C unless otherwise specified.
[0010] In this specification, unless otherwise specified, weight-average molecular weight and number-average molecular weight are polystyrene-converted values measured by GPC (gel permeation chromatography). In this specification, "film" and "sheet" refer to molded articles that are thin in thickness relative to their length and width, and are generally flat. Furthermore, "film" and "sheet" in this specification may be single-layer or multi-layer. If the measurement methods and the like described in the standards specified in the present specification differ by year, the standards as of January 1, 2024 shall apply unless otherwise specified. If the measurement methods and the like described in the standards specified in the present specification have been abolished as of January 1, 2024, the standards at the time of abolition shall apply. In Figures 1 to 2, scales and the like may not be consistent with actual dimensions.
[0011] <Polarizing Sheet> The polarizing sheet of the present embodiment has a first resin layer, a polarizing film, and a second resin layer in the stated order, wherein a glass transition temperature Tg1 (unit: °C) of the first resin layer and a glass transition temperature Tg2 (unit: °C) of the second resin layer satisfy Tg2-Tg1≧-1, and a retardation (Re1) of the first resin layer and a retardation (Re2) of the second resin layer respectively satisfy 2500nm≦Re1≦8000nm and 0≦Re2≦500nm. With such a configuration, a polarizing sheet having a low intersection temperature and excellent formability can be obtained. By setting the relationship between the glass transition temperatures of the first resin layer and the second resin layer to Tg2-Tg1≧-1, the intersection temperature of the X-curve value and the Y-curve value can be lowered. In order to prevent polarization leakage (rainbow unevenness), one of the resin layers on both sides of the polarizing film in the polarizing sheet needs to have high retardation. Therefore, in the present embodiment, the retardation (Re1) of the first resin layer is set to be high. Such high retardation is usually achieved by stretching the first resin layer. However, since the stretched first resin layer tends to shrink in the stretching direction during thermal bending, the X-curve value tends to be larger than the Y-curve value. In the present embodiment, by setting the glass transition temperature Tg2 of the second resin layer to a relatively high value, the second resin layer is less likely to change even in the temperature range where the first resin layer starts to shrink, so it is presumed that the second resin layer acts in a direction of suppressing the shrinkage force of the first resin layer, thereby improving the thermal bending processability. As a result, it is presumed that a polarizing sheet that can be thermally bent even with a curve having a radius of curvature of about 66 mmR, has a low intersection temperature, and is excellent in formability was obtained.
[0012] The embodiments of the present invention will be described in detail below, but the description of the constituent elements described below is merely one example of an embodiment of the present invention and is not limited to these.
[0013] The polarizing sheet of this embodiment has a first resin layer, a polarizing film, and a second resin layer in the order described above, and the glass transition temperature Tg1 (unit: °C) of the first resin layer and the glass transition temperature Tg2 (unit: °C) of the second resin layer are Tg2 - Tg1 ≥ -1. The glass transition temperature preferably satisfies Tg2-Tg1≧0, and more preferably satisfies Tg2-Tg1>0. Furthermore, the glass transition temperature preferably satisfies 20≧Tg2-Tg1, more preferably 16≧Tg2-Tg1, even more preferably 10≧Tg2-Tg1, even more preferably 7≧Tg2-Tg1, and even more preferably 5≧Tg2-Tg1. Setting it above the lower limit tends to broaden the temperature range in which the X-curve value and Y-curve value are similar, thus widening the process window. Also, setting it below the upper limit tends to improve morphability.
[0014] The glass transition temperature Tg1 of the first resin layer is preferably 120°C or higher, more preferably 125°C or higher, even more preferably 130°C or higher, even more preferably 135°C or higher, even more preferably 140°C or higher, and also preferably 160°C or lower, and more preferably 155°C or lower. Setting it above the lower limit tends to further improve the heat resistance as a polarizing sheet. Conversely, setting it below the upper limit tends to allow for a lower heat bending temperature.
[0015] The glass transition temperatures of the first and second resin layers shall be those measured by the method described in the examples below. Furthermore, the glass transition temperatures of the first and second resin layers can be adjusted by selecting the type of resin contained in each layer or by adding additives (other components described below). In this embodiment, the glass transition temperature is measured according to the description in the examples below (the same applies to the glass transition temperature hereafter). In this specification, the glass transition temperature refers to the midpoint glass transition temperature (Tmg).
[0016] In this embodiment, the retardation of the first resin layer (Re1) and the retardation of the second resin layer (Re2) satisfy 2500nm ≤ Re1 ≤ 8000nm and 0 ≤ Re2 ≤ 500nm, respectively. The retardation (Re1) of the first resin layer is preferably 3000 nm or greater, and preferably 6000 nm or less. The retardation (Re1) of the first resin layer is achieved by using a stretched film for the first resin layer. The stretching ratio of the first resin layer is preferably 1.1 times or more in the X direction, more preferably 1.3 times or more, and preferably 2.0 times or less, and more preferably 1.8 times or less. The stretching ratio of the first resin layer in the Y direction is preferably smaller than the stretching ratio in the X direction, and may be 1.1 times or less.
[0017] The retardation (Re2) of the second resin layer may be 10 nm or more, 100 nm or more, or 300 nm or less. The retardation (Re2) of the second resin layer is preferably achieved by using an unstretched film.
[0018] Regarding the method for manufacturing the first resin layer and the second resin layer film, and the method for stretching the film, known methods can be employed, and reference can be given to paragraphs 0062 to 0065 of Japanese Patent Application Publication No. 2024-101781, which are incorporated herein by reference. For example, by manufacturing film using a roll-to-roll method and adjusting the line speed of the rolls during film production, stretched film can be manufactured. Furthermore, while uniaxial or biaxial stretching is acceptable, uniaxial stretching is preferable.
[0019] In the polarizing sheet of this embodiment, the thickness of the first resin layer and the thickness of the second resin layer are preferably 100 μm or more, more preferably 200 μm or more, and preferably 500 μm or less, and more preferably 400 μm or less, independently of each other. In the polarizing sheet of this embodiment, it is preferable that the ratio of the thickness T1 of the first resin layer to the thickness T2 of the second resin layer (T2 / T1) satisfies 0.8 ≤ T2 / T1 ≤ 1.2.
[0020] In this embodiment, the first resin layer and the second resin layer each independently contain a resin, but preferably contain polycarbonate and / or polyamide, and more preferably contain polycarbonate.
[0021] If the first resin layer and / or the second resin layer contains polycarbonate, it is preferable that it be aromatic polycarbonate. The aromatic polycarbonate used in this embodiment is, for example, a polycarbonate in which 80% by mass or more of the constituent units are derived from aromatic monomers. The proportion of constituent units derived from aromatic monomers in the polycarbonate used in this embodiment is preferably 85% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 99% by mass or more. Examples of the aromatic monomers include bisphenol A, bisphenol C, and bisphenol AP, with bisphenol A and / or bisphenol AP being preferred, and bisphenol A being more preferred. An example of the aromatic polycarbonate used in this embodiment is a resin containing the constituent unit represented by formula (A) in a proportion of 80% by mass or more of the total constituent units. In the aromatic polycarbonate used in this embodiment, the proportion of the constituent unit represented by formula (A) may be 100% by mass, excluding the end groups. Formula (A) [ka] In equation (A) above, n is any number.
[0022] The diol components constituting the aromatic polycarbonate used in this embodiment include, in addition to 4,4'-isopropylidenediphenol, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)ketone, 1,1-bis(4-hydroxyphenyl)ethane, bisphenol A, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxy- Examples include 3,5-dibromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane, and a,ω-bis[3-(ο-hydroxyphenyl)propyl]polydimethylsiloxane.
[0023] Aromatic polycarbonates may include aromatic polycarbonates having the terminal structure represented by formula (C). [ka] (In formula (C), R 1 R represents an alkyl group with 8 to 36 carbon atoms, or an alkenyl group with 8 to 30 carbon atoms. 2 Each of these independently represents a halogen atom, an alkyl group with 1 to 20 carbon atoms, or an aryl group with 6 to 12 carbon atoms. n represents an integer from 0 to 4. * indicates a bonding site with another part. By using an aromatic polycarbonate having the terminal structure represented by formula (C), the glass transition temperature of the polycarbonate can be lowered. The aromatic polycarbonate having the terminal structure represented by formula (C) is preferably a bisphenol A type polycarbonate having the terminal structure represented by formula (C). Details of aromatic polycarbonates having the terminal structure represented by formula (C) can be found in paragraphs 0020 to 0025 of Japanese Patent Application Publication No. 2024-029933, the contents of which are incorporated herein by reference.
[0024] The molecular weight of the aromatic polycarbonate used in this embodiment is not particularly specified, but it is preferably 10,000 or more in viscosity-average molecular weight [Mv], preferably 100,000 or less, and more preferably 70,000 or less. By setting the viscosity-average molecular weight to be above the lower limit, the strength of the resulting polarizing sheet can be increased. Furthermore, by setting the viscosity-average molecular weight to be below the upper limit, the moldability tends to improve. In this embodiment, two or more aromatic polycarbonates with different viscosity-average molecular weights may be mixed and used; in this case, the viscosity-average molecular weight of the mixture shall be used. The viscosity-average molecular weight is measured by the method described in the examples.
[0025] The glass transition temperature of the aromatic polycarbonate used in this embodiment is preferably 160°C or lower, more preferably 155°C or lower, even more preferably 154°C or lower, even more preferably 153°C or lower, and even more preferably 152°C or lower. Furthermore, the glass transition temperature of the aromatic polycarbonate used in this embodiment may be, for example, 128°C or higher, and may also be 130°C or higher, 135°C or higher, or 140°C or higher. In this embodiment, if the first resin layer and / or the second resin layer contains two or more aromatic polycarbonates, the glass transition temperature of the aromatic polycarbonates is the sum of the values obtained by multiplying the glass transition temperature of each aromatic polycarbonate by its mass fraction.
[0026] Further details regarding aromatic polycarbonates can be found in paragraphs 0011-0020 of Japanese Patent Application Publication No. 2012-144604 and paragraphs 0014-0035 of Japanese Patent Application Publication No. 2019-002023, without departing from the spirit of this embodiment, and these contents are incorporated herein.
[0027] It is also preferable to use polycarbonate manufactured using biomass raw materials (biomass polycarbonate). By using biomass polycarbonate, the environmental impact can be reduced. Polycarbonate can also be made using monomer raw materials that have been certified under Mass Balance Certification (ISCC PLUS). Mass Balance Certification means that the extent to which renewable or bio-raw materials are used in each factory or production facility, and how much of the product is produced or shipped, is quantified and guaranteed along with the quality. Furthermore, the polycarbonate may be recycled (including collected materials, material recycled materials, chemical recycled materials, etc.), rejected materials, or scraps generated during the molding of polyamide.
[0028] On the other hand, if the first resin layer and / or the second resin layer contains polyamide, it is preferable that the polyamide contains amorphous polyamide. As amorphous polyamides, polyamides containing alicyclic diamine units and aliphatic dicarboxylic acid units are preferred. Details of amorphous polyamides can be found in paragraphs 0011-0023 of International Publication No. 2025 / 023088, which are incorporated herein by reference.
[0029] Examples of polyamides include GLILAMID TR FE5577, TR90, XE 3805, XE4205 (manufactured by EMS), NOVAMID X21 (manufactured by DSM), Toyobo Nylon T-714E (manufactured by Toyobo), G850 (manufactured by Arkema), and G850LV (manufactured by Arkema).
[0030] The polycarbonate and / or polyamide content in the first resin layer and / or second resin layer is preferably 85% by mass or more, more preferably 90% by mass or more, even more preferably 94% by mass or more, even more preferably 96% by mass or more, even more preferably 97% by mass or more, and 100% by mass or less, based on 100% by mass of the resin layer. When the first resin layer and / or the second resin layer contain two or more types of polycarbonate and / or polyamide, it is preferable that the total amount be within the above range.
[0031] The first resin layer and / or the second resin layer may contain other components without departing from the spirit of the present invention. Examples of other components include polyetheramide elastomers, mold release agents (fatty acid amides, fatty acid esters, polyalkylene glycols, etc.), ultraviolet absorbers, antioxidants, heat stabilizers, flame retardants, flame retardant additives, colorants, antistatic agents, fluorescent whitening agents, antifogging agents, flow modifiers, plasticizers, dispersants, antibacterial agents, antiblocking agents, impact modifiers, sliding modifiers, hue modifiers, acid trapping agents, etc. The content of these other components in the first resin layer and / or the second resin layer is preferably 0 to 5% by mass, more preferably 0 to 3% by mass, and even more preferably 0 to 2% by mass.
[0032] A known polarizing film can be used, and an example is one in which iodine or a dichroic organic dye is adsorbed or impregnated onto a polyvinyl alcohol (PVA) film. The thickness of the polarizing film is preferably 10 μm or more, preferably 100 μm or less, and preferably 50 μm or less.
[0033] The first resin layer and the second resin layer serve as the polarizing film substrate or polarizing film protective film of the polarizing sheet, and are usually bonded to the polarizing film via an adhesive. That is, an example of the polarizing sheet of this embodiment includes a multilayer body in which the first resin layer, adhesive layer, polarizing film, adhesive layer, and second resin layer are in contact with each other in the order described above.
[0034] The adhesive used to bond the first or second resin layer to the polarizing film can be a known adhesive, such as an acrylic adhesive, urethane adhesive, epoxy adhesive, silicone adhesive, or polyvinyl alcohol adhesive. Among these, urethane adhesives are preferred. The thickness of the adhesive is typically 1 μm or more, and typically 30 μm or less.
[0035] The total thickness of the polarizing sheet in this embodiment is preferably 535 μm or less, more preferably 530 μm or less, even more preferably 500 μm or less, even more preferably 495 μm or less, and also preferably 270 μm or more, more preferably 300 μm or more, and may be 350 μm or more or 400 μm or more depending on the application. By setting the total thickness of the polarizing sheet to the upper limit or less, the processing time during heat bending tends to be shortened. Also, by setting the total thickness of the polarizing sheet to the lower limit or more, the handling during heat bending tends to be improved. Furthermore, if the polarizing sheet of this embodiment has a multilayer body consisting of a first resin layer, an adhesive, a polarizing film, an adhesive, and a second resin layer, the total thickness of the multilayer body is preferably 535 μm or less, more preferably 530 μm or less, even more preferably 500 μm or less, even more preferably 495 μm or less, and also preferably 270 μm or more, more preferably 300 μm or more, and may be 350 μm or more or 400 μm or more depending on the application.
[0036] The polarizing sheet of this embodiment may have other layers besides those described above. Examples of other layers include a hard coat layer and an infrared absorption layer. Details of the hard coat layer will be described later.
[0037] The method for manufacturing the polarizing sheet is not particularly limited; for example, conventionally known methods can be used.
[0038] <Heat-bent molded product> The heat-bent molded body of this embodiment is obtained by heat-bending the polarizing sheet of this embodiment. Figure 2 is a schematic diagram showing an example of using the polarizing sheet of this embodiment in the manufacture of a heat-bent molded body, where 1 represents the second resin layer, 6 represents the polarizing film, 7 represents the first resin layer of this embodiment, and 8 represents the mold. In Figure 2, each component (1, 6, 7) is shown separately, but normally these components are bonded together with an adhesive to form a polarizing sheet, which is then placed in the mold 8. In this embodiment, it is preferable that the first resin layer side is a curved convex surface (the side indicated by the arrow in Figure 2), and the second resin layer side is a curved concave surface.
[0039] Furthermore, in this embodiment, the heat-bent molded body can be obtained by placing the polarizing sheet of this embodiment so that the first resin layer 7 is in contact with the mold (for example, a metal female mold) 8, reducing the pressure to make it adhere tightly to the mold 8, and obtaining an adsorbed punched piece. It is preferable to adsorb the polarizing sheet to the mold 8 and remove it from the mold 8 while adsorbing it using a male mold. Although the male mold used for adsorption to and removal from the mold is sometimes also referred to as a mold, the mold in this embodiment is a mold having a mold for the desired heat-bent shape.
[0040] The heat-bent molded article of this embodiment is preferably formed by heat-bending the polarizing sheet of this embodiment at a temperature of Tg1-30°C to Tg1-6°C, with reference to the glass transition temperature Tg1 of the first resin layer, and more preferably at a temperature of Tg1-15°C to Tg1-6°C. The heat bending temperature is more preferably Tg1-11°C or higher, even more preferably Tg1-10°C or higher, and even more preferably Tg1-7°C or lower.
[0041] <Hard coat layer> The polarizing sheet and heat-bent molded body of this embodiment may have a hard coat layer on their surface. In particular, when the polarizing sheet and heat-bent molded body of this embodiment are used in sunglasses, it is preferable to have a hard coat layer on the surface on the side where the lens is not provided. The hard coat layer is preferably obtained by applying a hard coat material that can be cured by heat or by active energy rays, and then curing it. Examples of materials (paints) cured using active energy rays include hard coat layers consisting of one or more monofunctional or polyfunctional (preferably 2 to 10-functional) (meth)acrylate monomers or oligomers, and preferably hard coat layers containing monofunctional or polyfunctional (preferably 2 to 10-functional) urethane (meth)acrylate oligomers. These hard coat layers preferably contain a photopolymerization initiator as a curing catalyst. Examples of thermosetting materials (paints) include polyorganosiloxane-based and cross-linked acrylic-based materials. Such hard coat materials are commercially available as hard coat agents for acrylic resin or polycarbonate resin films or sheets, and should be selected appropriately considering their suitability for the painting line. For the hard coat layer, reference can be given to paragraphs 0045 to 0055 of Japanese Patent Publication No. 2013-020130, paragraphs 0073 to 0076 of Japanese Patent Publication No. 2018-103518, and paragraphs 0062 to 0082 of Japanese Patent Publication No. 2017-213771, and these contents are incorporated herein by reference.
[0042] In addition to the above components, the hard coat layer may also contain light stabilizers, heat stabilizers, flame retardants, flame retardant additives, antistatic agents, fluorescent whitening agents, anti-fogging agents, flow modifiers, plasticizers, dispersants, antibacterial agents, antiblocking agents, impact modifiers, sliding modifiers, color modifiers, acid trapping agents, etc. One of these components may be used, or two or more may be used in combination.
[0043] The thickness of the hard coat layer is typically 1 to 10 μm.
[0044] <Application> The polarizing sheet or heat-bent molded article of this embodiment is preferably used as a polarizing sheet for liquid crystal display devices, a polarizing lens (sunglasses, ski goggles, prescription eyeglass lenses, camera viewfinder lenses), covers for various instruments, automobile glass, train glass, polarizing sheets for in-vehicle display panels and electronic equipment housings, in-vehicle rearview mirrors, and silver mirrors for helmets. The polarizing sheet or heat-bent molded article of this embodiment is particularly preferably used in sunglasses. [Examples]
[0045] The present invention will be described in more detail below with reference to examples. The materials, amounts used, proportions, processing content, and processing procedures shown in the following examples can be modified as appropriate, as long as they do not depart from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or other reasons, measurements can be taken using other instruments with equivalent performance.
[0046] <Polycarbonate used> E-1000: Bisphenol A type polycarbonate resin, manufactured by Mitsubishi Gas Chemical Company, Inc., glass transition temperature 154°C, viscosity-average molecular weight: 32,500 E-2000: Bisphenol A type polycarbonate resin, manufactured by Mitsubishi Gas Chemical Company, Inc., glass transition temperature 151°C, viscosity-average molecular weight: 27,000 S-3000: Bisphenol A type polycarbonate resin, manufactured by Mitsubishi Gas Chemical Company, Inc., glass transition temperature 149°C, viscosity-average molecular weight: 21,000 H-4000: Bisphenol A type polycarbonate resin, glass transition temperature 144°C, manufactured by Mitsubishi Gas Chemical Company. T-1380: Bisphenol A type polycarbonate resin using hexadecyl parahydroxybenzoate as a terminal encapsulant, manufactured by Mitsubishi Gas Chemical Company, Inc., glass transition temperature: 130°C, viscosity-average molecular weight: 25,500 LQ: Polyester-based plasticizer, TLQ 9KA014 GRY, manufactured by Toyo Color Co., Ltd.
[0047] <Measurement of glass transition temperature> The glass transition temperature of resins or resin compositions was determined in accordance with JIS K7121. A 10 mg sample was taken, and the midpoint glass transition temperature (Tmg) was measured. Specifically, a differential scanning calorimetry (DSC-60A, Shimadzu Corporation) was used to obtain a DSC curve under the following conditions: the sample was first heated to 230°C, then cooled to room temperature (below 30°C) at a rate of 20°C / min, and then heated again from room temperature to 230°C at a rate of 10°C / min. The midpoint glass transition temperature (Tmg) obtained from the resulting DSC curve was defined as the glass transition temperature.
[0048] <Measurement of viscosity-average molecular weight> The viscosity-average molecular weight [Mv] is given by Schnell's viscosity formula, i.e., η = 1.23 × 10⁻⁶. -4 Mv 0.83 It was calculated from that. The intrinsic viscosity [η] (unit dL / g) of polycarbonate was measured using methylene chloride as the solvent. The temperature was set at 25°C. The specific viscosity [η] at each solution concentration [C] (g / dL) was measured using an Ubbelohde viscometer. sp The specific viscosity was measured. The intrinsic viscosity was calculated from the obtained specific viscosity and concentration using the following formula.
number
[0049] <Manufacturing of polycarbonate film> As described in Table 1 or Table 2, polycarbonate or polycarbonate blended with the above LQ was extruded in a molten state using a T-die melt extruder consisting of a vented single-screw extruder (manufactured by Shibaura Machinery Co., Ltd.) with a screw nominal diameter of 50 mm and a screw L / D = 31.6, at a screw rotation speed of 115 rpm. After being compressed between the first and second rolls, the film was cooled and solidified to produce a film. The cylinder temperature was 280°C, the die temperature was 300°C, and the roll temperature was 120°C. The thickness was adjusted by the line speed to obtain a film with a thickness of 375 μm as the raw material (pre-stretched film) for the first resin layer and a film with a thickness of 300 μm for the second resin layer. The details of the first and second rolls used are as follows. For the polycarbonate blended with LQ, the above polycarbonate was pre-blended with 1 mass% of LQ. • First roll: Manufactured by Shibaura Machine Co., Ltd., UM roll Dimensions: Outer diameter 300mm x Roll width 600mm • Second roll: Manufactured by Shibaura Machine Co., Ltd., rigid metal roll (surface: chrome treated) Dimensions: Outer diameter 300mm x Roll width 600mm
[0050] <Manufacturing of the first resin layer> The raw material obtained as described above was uniaxially stretched using an offline uniaxial stretching machine (manufactured by Ichikin Kogyo Co., Ltd.) to obtain a film with a thickness of 300 μm and retardation as shown in Table 1. The stretching booth temperature was set to 150°C, and the stretching ratio was adjusted so that the film thickness after stretching was 300 μm.
[0051] <Measurement of film retardation (Re)> The film obtained above was cut to a size of 50 x 150 mm, and retardation was measured at a measurement wavelength of 543 nm. The unit is shown in nm. Retardation measurements were performed using a WPA-100 from Photonic Lattice.
[0052] Examples 1-6, Comparative Examples 1, 2 <Fabrication of polarizing films> A polyvinyl alcohol film (manufactured by Kuraray Co., Ltd.) was swollen in water at 35°C, then stained in an aqueous solution at 35°C containing the dichroic dyes Kayaras Blue G (CI Blue 78), Sumilight Red 4B (CI Red 81), chrysophenine (CI Yellow 12), and 10 g / L of anhydrous sodium sulfate. The film was then immersed in an aqueous solution at 35°C containing 2.5 g / L of nickel acetate and 5 g / L of boric acid, and finally stretched to four times its original size. The film was then heat-treated at 110°C for 3 minutes while maintaining tension to obtain a 30 μm polarizing film. The obtained polarizing film was stored in a low-humidity storage cabinet until the next process.
[0053] <Fabrication of polarizing sheets (multilayer)> A two-component moisture-curing polyurethane adhesive (main component: Mitsui Chemicals, "Takelac A-520", curing agent: Mitsui Chemicals, "Takenate A-50") was applied to one side of the first resin layer shown in Table 1 or Table 2, and the polarizing film obtained above was laminated with the stretch axis aligned. The remaining side of the polarizing film was laminated in the same manner using the second resin layer shown in Table 1 or Table 2. After lamination, the adhesive was cured by leaving the material in a 70°C constant temperature bath to obtain a polarizing sheet (multilayer). The thickness of the adhesive was 10 μm for each layer.
[0054] <Creating punched-out pieces> The polarizing sheet obtained above was punched out using a Thomson blade (Noda Corporation) and a hydraulic clicker (TC-55, Toko Corporation) to create punched pieces. The punched pieces were punched into a barrel shape of 80 mm x 60 mm as shown in Figure 1, with the longitudinal direction of the punched piece being the X direction (polarization axis direction).
[0055] <Heat bending properties (crossover temperature)> The heat bending process was carried out using a batch-type heat bending machine. At a predetermined temperature, the punched-out piece obtained above was placed in a metal female die having a partially spherical surface with a predetermined curvature, with the first resin layer in the multilayer body in contact with the metal female die. The piece was then pressed with a silicone rubber male die, and at the same time, the pressure was reduced to cause it to adhere to the metal female die. The punched-out piece was held in the mold at the predetermined temperature for a predetermined time, and then removed from the metal female die. In the above, a metal female die with a partially spherical surface equivalent to 8R (radius of curvature approximately 65.4 mm) was used, and the holding time was 4 minutes. The predetermined temperature for determining the crossover temperature was the actual temperature of the metal female die, which was adjusted by the temperature of the heat transfer medium. The X-curve and Y-curve values of the punched pieces after processing were measured using a curve meter (manufactured by Sun Nishimura Co., Ltd.). The temperature at which the X-curve value and the Y-curve value intersected was defined as the crossover temperature. If no crossover temperature was observed within the measured temperature range (100°C to 145°C), it was recorded as "no crossover."
[0056] <Heat-bending properties (shape-forming properties)> In the above-described heat bending process, the curve values at the crossover temperature were similarly measured, and the radius of curvature R of the punched piece was compared and evaluated against the radius of curvature R of the die. The evaluation was conducted by five experts, and Example 6 was judged to have a rating of "B" by majority vote. The evaluation was as follows: A: Excellent excipient properties B: The excipients were not sufficient. C: No cross-temperature
[0057] [Table 1]
[0058] [Table 2]
[0059] In the above, "+LQ1%" indicates that LQ has been added to the polycarbonate at a ratio of 1% by mass.
[0060] As is clear from the above results, the polarizing sheets of the present invention had a low crossover temperature and excellent shapeability (Examples 1-6). In contrast, the polarizing sheets of Comparative Examples 1 and 2, which did not satisfy Tg2-Tg1≧-1, did not have a temperature at which the X-curve value and Y-curve value intersected in the temperature range of 100-145°C, and could not be heat-bent when using a mold with R8.
[0061] Although the present invention has been described in detail using specific embodiments, it will be apparent to those skilled in the art that various modifications are possible without departing from the intent and scope of the invention. [Explanation of Symbols]
[0062] 10 cut polarizing sheets (punched pieces) 1 Second resin layer 6 Polarizing film 7 First resin layer 8 molds
Claims
1. The first resin layer, the polarizing film, and the second resin layer are arranged in the order described above. The glass transition temperature Tg1 (unit: °C) of the first resin layer and the glass transition temperature Tg2 (unit: °C) of the second resin layer are, Tg2-Tg1≧-1 Satisfying the conditions, The retardation of the first resin layer (Re1) and the retardation of the second resin layer (Re2) are, respectively, 2500 nm ≤ Re1 ≤ 8000 nm, and 0 ≤ Re2 ≤ 500 nm A polarizing sheet that satisfies the requirements.
2. The polarizing sheet according to claim 1, wherein the glass transition temperature Tg1 of the first resin layer and the glass transition temperature Tg2 of the second resin layer satisfy Tg2 - Tg1 ≥ 0.
3. The polarizing sheet according to claim 1, wherein the glass transition temperature Tg1 of the first resin layer and the glass transition temperature Tg2 of the second resin layer satisfy Tg2 - Tg1 > 0.
4. The polarizing sheet according to any one of claims 1 to 3, wherein the thickness of the first resin layer and the thickness of the second resin layer are each independently 100 to 500 μm.
5. The polarizing sheet according to any one of claims 1 to 3, wherein the first resin layer and the second resin layer each independently contain polycarbonate and / or polyamide.
6. The polarizing sheet according to any one of claims 1 to 3, wherein the first resin layer is a stretched film and the second resin layer is a non-stretched film.
7. The glass transition temperature Tg1 of the first resin layer and the glass transition temperature Tg2 of the second resin layer satisfy Tg2 - Tg1 > 0, The thickness of the first resin layer and the thickness of the second resin layer are, independently, 100 to 500 μm. The first resin layer and the second resin layer each independently contain polycarbonate and / or polyamide. The first resin layer is a stretched film, and the second resin layer is an unstretched film. The polarizing sheet according to claim 1.
8. A heat-bent molded polarizing sheet according to any one of claims 1 to 3 and 7.
9. The heat-bent molded article according to claim 8, wherein the first resin layer side is a curved convex surface and the second resin layer side is a curved concave surface.
10. Sunglasses comprising the heat-bent molded body described in claim 8.
Citation Information
Patent Citations
Protective film for polycarbonate plate
JP2003145616A